2020
DOI: 10.2196/18123
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Perspectives and Design Implications in Using Patient-Generated Health Data to Improve Mental Health Practices: Mixed Methods Study

Abstract: Background Patient-generated health data (PGHD) have been largely collected through mobile health (mHealth) apps and wearable devices. PGHD can be especially helpful in mental health, as patients’ illness history and symptom narratives are vital to developing diagnoses and treatment plans. However, the extent to which clinicians use mental health–related PGHD is unknown. Objective A mixed methods study was conducted to understand clinicians’ perspective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…Some studies [16,17] reported about the adaptation of standards for integration of data from wearables into EHRs, in particular HL7 Common Document Architecture (CDA). Other studies point out the limited capacity of EHRs for direct patient input [18], insufficient integration of mental health apps with EHRs [19], and EHRs being inferior at storing patient contextual data such as patients' needs, values, goals, and preferences relevant to their care [20]. This limited support for direct patient engagement was confirmed in the recent FHIR connectathon, in the Patient Empowerment track.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies [16,17] reported about the adaptation of standards for integration of data from wearables into EHRs, in particular HL7 Common Document Architecture (CDA). Other studies point out the limited capacity of EHRs for direct patient input [18], insufficient integration of mental health apps with EHRs [19], and EHRs being inferior at storing patient contextual data such as patients' needs, values, goals, and preferences relevant to their care [20]. This limited support for direct patient engagement was confirmed in the recent FHIR connectathon, in the Patient Empowerment track.…”
Section: Resultsmentioning
confidence: 99%
“…When patients present CST data to clinicians, there may be disagreements on how patient-generated health data (PGHD) should be used [ 20 , 21 ]. One systematic review found that PGHD improved clinicians’ understanding of patients’ health, but clinicians had a varied interest in PGHD and encountered barriers to its use in clinical care, such as time constraints, lack of workflow integration, information overload, and lack of reimbursement [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These challenges include the lack of actionable data, reliability and accuracy of the data, workflow disruption, technical issues, and a lack of incentives. 8,98,99 Furthermore, food practice data need to be summarized, so that patterns can be easily visualized by health care professionals who will eventually need to rapid sense making and decision-making. 100,101 Perceived or objective problems with the reliability and accuracy of data can affect use of food practice data.…”
Section: Presenting Contextualized Food Practice Data To Cliniciansmentioning
confidence: 99%